Efficient removal of lead(II) ions in water using functionalized poly(styrene) oligomers - Sánchez Anguiano , Maria G.; Oliva de Dios, Mauricio L.; Chan Navarro, Rodrigo; Elizondo Martínez, Perla; Rosa M.; García López , María Concepción (Quimica Hoy, 2023)
In this research, chemically functionalized polystyrene oligomers with acrylamide monomers were applied as alternative adsorbent towards Pb(II) from aqueous solutions. Adsorption process of Pb(II) was optimized using the 2*' fractional factorial design with replicates at the central point supplemented with the central composite design where the percentage adsorption was chosen as the response variable. This variable was simultancously optimized using the desirability functions approach to select the best conditions for the adsorption process. The experimental data reveal that after the optimization, the maximal response was exhibited at 38 °C, pH 5.80, initial adsorbate concentration (36.40 mg L™, and adsorbent dosage (10.77 mg) with the desirability function of 0.9260. Theoretical values and experimental data determined by the central composite design showed a high correlation with a R? value of 0.9810. Under these optimal conditions, the theoretical value for the removal of Pb(II) was 93.12%, while that experimental assay gives a maximum value of 91.23%. Likewise, the analysis of surface charge distribution, the structural and morphological characteristics confirmed the successful chemical modification of poly(styrene) oligomers.